Teaching Methodology Ensuring the Coherence of Economic Sciences - Ergashev Khudoynazar Khabibullaevich (Genius Journals, 2022)
Economics as a subject began to appear in Uzbekistan in the mid-1990s. During this short period, teaching economics at institute not only was not stopped, but, on the contrary, began to develop rapidly in almost all universities and institutes, and the interest of teachers, students and their parents is growing every day. In Uzbekistan, the study of economics is currently carried out mainly only at the last stage of education - at the level of higher professional education in many universities of the country. The purpose of the article is to study the organizational and methodological process of teaching economics in universities, institutes, and schools
Keywords: policy; organizational structure; strategy; accounts